2008
DOI: 10.1029/2007jd009263
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of evapotranspiration and energy exchange over an annual grassland in California

Abstract: [1] We report on the interannual variability of evapotranspiration (E) and energy exchange of an annual grassland in the Mediterranean climate zone of California. They were measured directly with the eddy covariance technique over a 6-year period that spanned between July 2001 and June 2007 and experienced a large range in precipitation (376 mm to 888 mm). Despite a two-fold range in precipitation, annual E ranged much less, between 266 mm and 391 mm. We found that pronounced energy-limited and water-limited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 134 publications
11
131
1
4
Order By: Relevance
“…In a study on global ET linkages to MAT and precipitation during the 1982-2008 period, Jung et al (2010) declared that precipitation dominated inter-annual ET behavior in northern China, but in southern China ET was mainly temperature limited. ET in the semi-arid and arid northern areas of China was limited by the supply of soil moisture, which is significantly affected by precipitation, the key constraining factor of ET here (Ryu et al, 2008;Wang and Dickinson, 2012). Using daily meteorological data and gauging station data, Zhang et al (2011b) indicated that precipitation was the major determinant of ET in the YeRB.…”
Section: Linkage Of Et To Climate Factorsmentioning
confidence: 99%
“…In a study on global ET linkages to MAT and precipitation during the 1982-2008 period, Jung et al (2010) declared that precipitation dominated inter-annual ET behavior in northern China, but in southern China ET was mainly temperature limited. ET in the semi-arid and arid northern areas of China was limited by the supply of soil moisture, which is significantly affected by precipitation, the key constraining factor of ET here (Ryu et al, 2008;Wang and Dickinson, 2012). Using daily meteorological data and gauging station data, Zhang et al (2011b) indicated that precipitation was the major determinant of ET in the YeRB.…”
Section: Linkage Of Et To Climate Factorsmentioning
confidence: 99%
“…[16] In this example, we apply the method to the Vaira Ranch data set of the Ameriflux network [Ryu et al, 2008] where measured evaporation flux data is available for verification. The site is located in California (N38.4067/ W120.9507, elevation 129m).…”
Section: Example Of Methodologymentioning
confidence: 99%
“…[5] Below we demonstrate the method at the Vaira Ranch Ameriflux site [Ryu et al, 2008] using field measured atmospheric forcing and remotely sensed soil moisture (AMSR-E derived LPRM [Owe et al, 2008] product) and Leaf Area Index (MODIS level 4 product available through the USGS Land Processes Distributed Active Archive Center). To keep the parameter estimation manageable for large scale applica-1 tions, we start with default soil and vegetation parameters sets and then further refine key parameters within these sets.…”
Section: Introductionmentioning
confidence: 99%
“…The PAR albedo is related to plant greenness and scales negatively with leaf area index, implying that it can capture the phenological events and canopy structure [32] . The spikes in the flux data were removed [33] , then small gaps were filled using linear interpolation, while large gaps were filled using the gap-filling methodology presented by ref.…”
Section: Measurementmentioning
confidence: 99%